Isolated Bone Recurrence of Medulloblastoma With MYCN Amplification and TP53 Loss: A Case Report. Issue 2 (March 2022) - Takahashi, Yuka; Kudo, Ko; Ogawa, Kaoru; Sato, Tomohiko; Kamio, Takuya; Sasaki, Shinya; Kobayashi, Akie; Ito, Tatsuya; Yamamoto, Tatsuya; Asano, Kenichiro; Ohkuma, Hiroki; Kurose, Akira; et al.
Abstract : Extraneural recurrence of a medulloblastoma is rare with dismal prognosis. A 9-year-old girl with medulloblastoma was treated with gross total resection followed by a combination of chemotherapy and radiotherapy. Fourteen months after treatment completion, she developed multifocal bone metastases. Despite chemotherapy combined with irradiation, she died 18 months after recurrence due to progressive disease. Fluorescence in situ hybridization on formalin-fixed paraffin-embedded tissue sections revealed MYCN amplification and TP53 loss, consistent with the genetic alterations of a rapidly progressive subgroup of recurrent medulloblastomas. In clinical practice, dismal biologic features can be determined using fluorescence in situ hybridization in defective materials.